PENGARUH BLENDED LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SD NEGERI 050653 BUKIT LAWANG - Laila Sakdah (CV. Arsy Persada Quality, 2025)
Blended learning refers to learning that combines or mixes face-to-face learning and internet-based learning (online). With blended learning and learning independence, students are expected to improve learning outcomes, especially in Islamic Religious Education. The aim of this research is (1) to determine the effect of blended learning on Islamic Religious Education learning outcomes (2) to determine the effect of learning independence on Religious Education learning outcomes. Islam: (3) to determine the effect of blended learning and student learning independence together on student learning outcomes. This research took place at SD Negeri 050653 Bukit Lawang. This research is a quantitative study with a population of 244 people and a sample size of 150 people determined using the Slovin method. The research results show that (1) There is a positive and significant influence between blended learning on Islamic Religious Education learning outcomes. Blended learning has an influence on Islamic Religious Education learning outcomes of 6.1% and the remaining 93.9% is determined by other factors; (2) There is a positive and significant influence between learning independence on Islamic Religious Education learning outcomes. Learning independence has an influence on results studying Islamic Religious Education amounted to 6.1% and the remaining 93.9% was determined by other factors; (2) There is a positive and significant influence between learning independence on Islamic Religious Education learning outcomes. Learning independence has an influence on Islamic Religious Education learning outcomes by 10.3% and the remaining 89.7% is determined by other factors; (3) There is a positive and significant influence between blended learning and independent learning together on Islamic Religious Education learning outcomes. Blended learning and independent learning together influence Islamic Religious Education learning outcomes by 16.5% and the remaining 83.5% is determined by other factors.